2013
DOI: 10.1007/s00232-013-9561-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum Myeloperoxidase Activity, Total Antioxidant Capacity and Nitric Oxide Levels in Patients with Chronic Otitis Media

Abstract: It has been suggested that oxidative stress may play an important role in the pathogenesis of chronic otitis media (COM), but the role of oxidative stress in the pathogenesis of COM has not yet been fully explored. Therefore, the aim of this study was to investigate serum myeloperoxidase (MPO) activity, 4-hydroxynonenal (4-HNE), malondialdehyde (MDA), total antioxidant capacity (TAC) and nitric oxide (NO) in patients with COM. Sixty-one patients with COM and 30 controls were enrolled in the present study. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 30 publications
0
22
0
2
Order By: Relevance
“…Chronic otitis media (COM) is a common disease with some severe complications that result from long-standing damage to the middle ear by inflammation or infection [1] . Although the etiopathogenesis of COM has not been fully elucidated to date, genetic, inflammatory, autoimmune, and infectious factors, including cytokines, endotoxins, and oxidative stress, have been implicated [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic otitis media (COM) is a common disease with some severe complications that result from long-standing damage to the middle ear by inflammation or infection [1] . Although the etiopathogenesis of COM has not been fully elucidated to date, genetic, inflammatory, autoimmune, and infectious factors, including cytokines, endotoxins, and oxidative stress, have been implicated [2] .…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with that in the WT mice, significantly lower levels of NF-κB, TNF-α, MIP1α, MUC5AC, and MUC5B, but higher levels of SOD, MPO, iNOS and caspase3 expression were detected in the MEs of Tlr2 −/− mice. The altered expression levels of these genes may be associated with impairment of macrophage recruitment and mucin protection, inducing oxidative stress and ciliated cell apoptosis, supporting the notion that oxidative stress is involved in the pathogenic process of OM (Garca et al, 2013; Testa et al, 2012). It is possible that PGPS in the absence of TLR2 stimulates inflammation and neutrophil accumulation that induce oxidative stress and tissue damage, and limit the recovery of OM and promote the chronic progression of OM in mice.…”
Section: Resultsmentioning
confidence: 64%
“…Moreover, Aksoy et al revealed an association of patients with allergic rhinitis to increased serum protein oxidation levels (Aksoy et al 2009(Aksoy et al , 2012. Other fi ndings add to the evidence that elevated serum oxidant levels and declined antioxidant status levels were observed in patients with chronic long-term otitis media (Garca et al 2013a ;Baysal et al 2013 ;Testa et al 2012 ).…”
Section: Select Misconceptions In Free-radical Biologymentioning
confidence: 79%
“…Truly reactive radicals are those chemical species with one or two highly reactive unpaired valence electrons in open electron shell(s). A large body of evidence suggests that free radicals are linked to the pathogenesis of tumors (Manjunath et al 2010 ;Valko et al 2006 ;Dwivedi et al 2008 ), hearing loss (Yamasoba et al 2013 ;Rewerska et al 2013 ), tonsillitis (Garca et al 2013b ;Cvetkovic et al 2009 ;Yilmaz et al 2004 ;Li et al 2011 ), allergic rhinitis (Aksoy et al 2009(Aksoy et al , 2012, chronic otitis media (Garca et al 2013a ;Baysal et al 2013 ;Testa et al 2012 ), and rhinosinusitis (Citardi et al 2006 ;Uslu et al 2003 ) and implies that antioxidant therapy eventually may be employed as a strategy to ameliorate these disorders and diseases (Ding et al 2013 ;Tian et al 2013 ;Someya et al 2010 ). As has been shown recently, however, many antioxidants that are effective in animal models are not effective in human clinical trials.…”
Section: Overview and Introductionmentioning
confidence: 98%